Evaluating the Distance Learning Experience During the Corona Pandemic Using the Multiple Decision Model (CIPP) - Field Study on Students of Saudi Universities- - Al-Hoshan, Amal Hoshan (Journal of Educational and Psychological Sciences, 2020)
The study aimed to evaluate the distance learning during the Corona pandemic using the Multiple Decision Model (CIPP), through evaluating the context, inputs, processes and outputs of the experience from the viewpoint of male and female students at the undergraduate level in Saudi universities. To achieve the goals of the study, the descriptive survey approach was used, and the questionnaire as a study tool that consisted of (22) phrases divided into four axes (context, inputs, processes, outputs). It was applied to a simple random sample consisting of (502) male and female students in the study population which included all male and female students of the public universities in the Riyadh region, who numbered (184, 035). The study found that the input axis was the highest achieved with a high degree (3.52), followed by the outputs with a medium degree (3.39), operations with a medium degree (3.26) and assessing the context with an average degree (3.23). A number of recommendations were given, the most important of which was developing the infrastructure and academic accreditation for distance education programs, and providing support students in financial need.